Cari turunan hasil bagi dari fungsi di atas
Jawab:
Penjelasan dengan langkah-langkah:
turunan bentuk y = u/v
y' = (u' v - uv' ) / v²
__
soal 1
y = (3x² -2x) / (x²)
y' = { (6x -2)(x²) – 2x (3x² -2x) } / (x²)²
y' = { 6x³ – 2x² – 6x³ + 4x²} / (x²)²
y' = 2x²/(x²)²
y' = 2/x²
soal 2
y= (x² – x) /( x+ 3)
y' = { (2x- 1)( x+ 3) – 1(x² – x) }/ ( x+ 3)²
y' = (2x² + 5x – 3 – x² + x ) / (x + 3)²
y' = ( x² + 6x – 3 ) / ( x+ 3)²
soal 3
y= (x³ – 2x) / (x²)
y' = { (3x²- 2)(x²) – 2x (x³ -2x) } / (x²)²
y' = (3x⁴ -2x² – 2x⁴ + 4x² ) / (x²)²
y' = (x⁴- 2x²) / (x²)²
y' = { x² (x² – 2 ) } / (x²)(x²)
y' = (x² – 2 ) / (x²)